Implementasi Program Agripreneurship IKA Faperta melalui Budidaya Okra Merah di Sadifa Farm Kabupaten Bogor - Sherly Eka Maulidiya; Suryo Wiyono; Octen Suhadi; Rina Mardiana; Winda Hidayatul Khairina; Khasanah Puspitaningtyas; Fadillah Abdul Fatah; Ayu Aulya Nurmala; Zahra Nurul Hidayah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Agripreneurship activities initiated by the Faculty of Agriculture Alumni Family Association (IKA Faperta), together with the Faculty of Agriculture, IPB University, are an effort to create young, independent agripreneurs with sustainable businesses. This activity is a forum for increasing student capacity through assistance in the agricultural business sector from upstream to downstream. IKA Faperta plays a role in assisting active students of the Faculty of Agriculture. In implementing this program, the parties involved were five active students from the Faculty of Agriculture as interns, 1 IPB alums as project managers, six as mentors, and 2 IPB lecturers. The method of implementing activities is carried out through four main stages: socialization, provision, field projects, and field trips. The demonstration plot was made at Sadifa Farm, Bogor Regency, with a land area of 10 x 15 m and a plant population of 250 red okra plants. Evaluation of changes in knowledge during participant debriefing is carried out through pre-test and post-test. Based on the IKA Faperta Agripreneurship activity results, this activity can encourage students to form a business unit based on agricultural products. It can increase experience and expertise in carrying out on-farm cultivation. Product marketing activities are also carried out by implementing two sales strategies: direct selling and digital marketing platforms. Product absorption is also optimized through collaboration with strategic partners, namely Agribusiness and Technology Park (ATP), a center for agricultural product innovation and a link to a broader market.